The predictive role of tendency toward mobile learning and emotional intelligence in Internet addiction in healthcare professional students - NAYEREH BAGHCHEGHI; HAMID REZA KOOHESTANI (Journal of Advances in Medical Education and Professionalism, 2022)
Introduction: Internet addiction is a psychological disorder that can lead to serious damages to university students as a group at risk. This study aimed to determine the predictive role of tendencytoward mobile learning (purposeful use of mobile technologies for educational purposes) and emotional intelligence in Internet addiction in healthcare professional students.Methods: A cross-sectional descriptive study was carried out on 403 healthcare professional students at Saveh University of Medical Sciences-Iran in 2021 using convenience sampling method. For data gathering, three questionnaires were used: willingness to use mobile learning, Young’s Internet Addiction Test, and the Emotional Intelligence Appraisal. Data analyses were done using Pearson Correlation Coefficient and Hierarchical Regression in SPSS 16 (Inc SPSS USA, IL, Chicago).Results: The mean age of the participants was 21.09±1.47 years; 125 subjects (31.01%) were boys and 278 (68.99%) girls. As the findings showed, 16.87% of the students had Internet addictionand 33% were on the edge of developing Internet addiction. Internet addiction was significantly negatively correlated with willingness to m-learning (r=-0.45, P=0.001) and emotional intelligence (r=-0.32, P=0.01). In addition, regression analysis results showed that the variables willingness to use learning and emotional intelligence explained 23% of the Internet addiction variance (p <0.001). Conclusion: In the present study, a considerable number of the healthcare professional students had excessive and unnecessary use of the Internet. Emotional intelligence and willingness to use mobile learning had an inverse relationship with Internet addiction. There is a need to screen Internet-addicted students using proper screening tools and take primary preventive measures in this regard. In addition, proper measures are needed to be taken to improve emotional intelligence and mobile learning skills and control Internet addiction to some extent.